Molecular identification and phylogenetic analysis of Cryptosporidium, Hepatozoon and Spirometra in snakes from central China. (December 2019) - Xiao, Xiao; Qi, Rui; Han, Hui-Ju; Liu, Jian-Wei; Qin, Xiang-Rong; Fang, Li-Zhu; Zhou, Chuan-Min; Gong, Xiao-Qing; Lei, Si-Cong; Yu, Xue-Jie
Abstract: Snakes are popular as food and traditional medicine in China. However, information about parasitic and bacterial infections in snakes from China is scarce. We investigated the prevalence of selected zoonotic agents including Cryptosporidium, Hepatozoon and Spirometra, in snakes in central China from June to October in 2018 by PCR amplification using parasite-specific primers. PCR amplification and DNA sequencing showed that 10.1% (15/149) of snakes were positive for Cryptosporidium spp., while 2.7% (4/149) were positive for Hepatozoon . Additionally, we found 36.9% (55/149) of snakes were infected with Spirometra erinaceieuropaei . The spargana burden per infected snake ranged from 1 to 26. BLAST and phylogenetic analysis of small subunit ribosomal RNA (SSU rRNA) gene and 60-kDa glycoprotein ( gp60 ) gene showed that the parasites belonged to Cryptosporidium parvum genotype IIdA15G1, C. baileyi, C. serpentis and a Hepatozoon species. We conclude that intensively farmed snakes excrete C. parvum and C. baileyi oocysts due to ingestion of infected feeder animals, and that wild snakes in central China were commonly infected with S. erinaceieuropaei, suggesting that eating improperly cooked snakes could be risky to human health. Graphical abstract: Image 1 Highlights: Cryptosporidium parvum and C. baileyi were reported in farmed snakes in China for the first time. C. serpentis was detected for the first time in Ptyas dhumnades and Gloydius brevicaudus. A tentative new Hapatozoon species was first time recorded in wild Lycodon rufozonatus and G. brevicaudus. Spirometra erinaceieuropaei infection was found common in wild snakes from central China.